Gemination and degemination in English affixation Investigating the interplay between morphology, phonology and phonetics - Ben Hedia, Sonia (Studies in Laboratory Phonology, 2019)
In English, phonological double consonants only occur across morphological boundaries, for example, in affixation (e.g. in unnatural, innumerous). There are two possibilities for the phonetic realization of these morphological geminates: Either the phonological double is realized with a longer duration than a phonological singleton (gemination), or it is of the same duration as a singleton consonant (degemination).